Effects of weather types on hospital admissions for respiratory diseases in Castilla-La Mancha, Spain - F. DE PABLO DÁVILA (Atmósfera, 2013)
The aim of this study is to evaluate the relationship between the risk of hospital admission for respiratory diseases (RD) and the daily weather types during the period 2000-2006. A synoptic climatological approach is used to investigate links between air-mass types (weather situations) and all respiratory hospital admissions in the Castilla-La Mancha (CLM) area in Spain. This afforded the main circulation weather types (CWTs) for the winter and spring periods (since respiratory hospital admissions reached their maximum during these seasons) and the frequency distributions of these types were analyzed. A summary of the main characteristics of the hospital admission series and their distribution over the seven years studied, together with the frequency distributions of the admissions classified by sex and ages, for season, month and for each day of the week, is reported. In addition, a comparison between air-mass classification and hospital admissions is made using an admission index (AI). The results reveal different responses of respiratory admission rates to the eight air-mass types identified in winter and in spring. In winter, three air massess southwesterly (SW), anti-cyclonic (A) and hybrid anti-cyclonic southwesterly (HASW), are associated with values 1.5 times higher than the respective average admission rates, while in spring no significant differences are seen.